(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The general well-being of the elderly might be negatively impacted by feelings of loneliness and social isolation. This study looks at the mediating roles of gender, marital status, and education level in the relationship between social isolation and loneliness and the psychological well-being of older adults living in different old-age homes in India. The sample size is 320 people, all of whom are 60 years old or older. Ryff and Keyes’s shorter version of the psychological well-being scale, the UCLA Loneliness Scale, and the Lubben Social Network Scale–6 were among the standardised measures used for data collection (1995). In order to comprehend the relationships between psychological health and social isolation or loneliness, researchers used multivariate and mediation analysis. Both social isolation (F = 3.836, p < .01) and loneliness (F = 3.782, p < .01) were shown to have a statistically significant MANOVA impact. Individuals’ psychological health was strongly related to their gender and level of education when considered as independent variables. Older persons’ mental health was unaffected by social isolation and loneliness regardless of their gender or level of education. In addition, the correlation between social isolation, loneliness, and mental health was somewhat moderated by marital status. Methods developed to help the elderly cope with loneliness and social isolation may make use of the study’s conclusions. The results may also inform the development of intervention programmes for the elderly, with the goals of rehabilitating their mental health and decreasing their rates of social isolation and loneliness.